The Influence Of Behavior, Motivation, And Independence Of Tax Inspectors On The Quality Of Tax Audits With Performance As An Intervening Variable - Taufik Susanto; Thresia Ernaz; Ida Rohmatika; Yessy Lola Aprillia (Publikasi Indonesia, 2023)
This study aims to analyze the influence of behavior, work motivation, and independence of tax inspectors on the quality of tax audits through tax inspector performance intermediaries. This research is included in descriptive quantitative research that prioritizes in-depth analysis of the data and facts found. The sampling technique uses the purposive sampling method for tax practitioners registered as members of the Indonesian Association of Academics and Tax Professionals, both employees who work in a company and tax consultants who have represented taxpayers in the tax audit process in DKI Jakarta with at least 3 years of work experience collected using questionnaires. The analysis technique used is Structural Equation Modeling (SEM). The results of the study show that behavior, work motivation,n, and independence have a positive and significant effect on the quality of tax audits. In addition, the performance of tax inspectors is only able to mediate the relationship between behavior and independence of the quality of tax whereas the performance of tax inspectors cannot mediate the relationship between work motivation and the quality of tax audits